Partial growth hormone insensitivity and dysregulatory immune disease associated with de novo germline activating STAT3 mutations. (15th September 2018) - Gutiérrez, Mariana; Scaglia, Paula; Keselman, Ana; Martucci, Lucía; Karabatas, Liliana; Domené, Sabina; Martin, Ayelen; Pennisi, Patricia; Blanco, Miguel; Sanguineti, Nora; Bezrodnik, Liliana; Di Giovanni, Daniela; et al.
Abstract: Germinal heterozygous activating STAT3 mutations represent a novel monogenic defect associated with multi-organ autoimmune disease and, in some cases, severe growth retardation. By using whole-exome sequencing, we identified two novel STAT3 mutations, p.E616del and p.C426R, in two unrelated pediatric patients with IGF-I deficiency and immune dysregulation. The functional analyses showed that both variants were gain-of-function (GOF), although they were not constitutively phosphorylated. They presented differences in their dephosphorylation kinetics and transcriptional activities under interleukin-6 stimulation. Both variants increased their transcriptional activities in response to growth hormone (GH) treatment. Nonetheless, STAT5b transcriptional activity was diminished in the presence of STAT3 GOF variants, suggesting a disruptive role of STAT3 GOF variants in the GH signaling pathway. This study highlights the broad clinical spectrum of patients presenting activating STAT3 mutations and explores the underlying molecular pathway responsible for this condition, suggesting that different mutations may drive increased activity by slightly different mechanisms. Highlights: WES performed in two unrelated patients reveals two novel STAT3 variants. Both variants were associated with severe growth failure and immune dysregulation. Functional studies showed they are activating variants. They respond differentially to growth hormone and interleukin-6 in in vitro assays. They partially impaired STAT5b transcriptional activity.